Simplified Mapreduce Mechanism for Large Scale Data Processing - Tahsir Ahmed Munna, Md; Muhammad Allayear, Shaikh; Mohtashim Alam, Mirza; Shah Mohammad Motiur Rahman, Sheikh; Samadur Rahman, Md; Mesbahuddin Sarker, M (International Journal of Engineering and Technology, 2018)
MapReduce has become a popular programming model for processing and running large-scale data sets with a parallel, distributed paradigm on a cluster. Hadoop MapReduce is needed especially for large scale data like big data processing. In this paper, we work to modify the Hadoop MapReduce Algorithm and implement it to reduce processing time.Â Â